Effect of Corn Type and Form of Supplement on Grazing Steers - J. K. Farney; T. Bottorff (Kansas Agricultural Experiment Station Research Reports, 2022)
Eighty stocker steers were grazed on bromegrass from April to the beginning of November and were provided five different feeds while on grass during the summer. Treatments evaluated included (1) mineral only; (2) free-choice supplementation in the form of liquid feed (MIX30) or (3) block format (Mintrate 40 Red); and hand-fed supplements of 60% corn:40% dried distillers grains at 0.5% of body weight on a dry matter basis offered daily where the corn was either an (4) isoline corn (ISO; parent genetic line) or (5) Enogen feed corn (ENO; includes alpha-amylase gene). Steers were weighed every 28 days while on grass and were carcass quality measured by ultrasound prior to placement in the feedlot. Hand-fed steers had greater gain than self-fed supplemented steers and these steers also had more backfat and tended to have more muscle depth coming off grass than other supplemented steers. Steers that received free-choice mineral or self-fed supplements also had lower gains than steers being hand-fed supplement. Within the first 28 days of the study, the hand-fed steers began weighing more and weighed 125 pounds more than the free-choice supplemented and control steers. On average hand-fed steers had a 0.6 lb/d greater ADG than control steers and those consuming free-choice supplement. Cost of gain was the highest with hand-fed steers at 0.27/pound, but even so profit was greatest with the hand-fed cattle.
Keywords: amylase corn; protein block; liquid feed; hand-fed